Hydraulic analysis and flood mitigation study of Estero de Paco - Dagdag, Alejandrino E.
In this research, the watershed hydrology and channel hydraulics of Estero de Paco were investigated and analyzed mainly for assessing possible flood mitigation alternatives, and partly improving the water quality condition of the estero. The properties of the watershed (sub-basins, reaches, etc.) that define the watershed properties of the estero affecting its hydrology were identified using geographic information system (GIS) spatial analysis. Hydrologic modeling for the conversion of rainfall to runoff was accomplished using Hydrologic Engineering Center - Hydrologic Modeling System (HEC-HMS). The Kinematic Wave Model was particularly used for handling the basin's overland runoff. Output discharges were then utilized for defining the initial and boundary conditions of the channel. Velocities, flow energies and water levels among others were computed using Hydrologic Engineering Center - River Analysis System (HEC-RAS). Based on model calibration and validation using data from Pasig River Rehabilitation Commission (PRRC), the hydraulic model of Estero de Paco performs within acceptable limits of accuracy. Three model simulation scenarios were investigated for attaining the objectives of this research; (1) downstream floodgate and pump operation; (2) dredging for river improvement and; (3) river flushing for water quality improvement. Results of the hydraulic modeling showed that the tidal boundary downstream along Pasig River governs Estero de Paco channel hydraulics during periods of no rainfall. Watershed runoff on the other hand becomes increasingly significant on the channel hydraulics with increasing upstream discharges. Channel improvement was also shown to have minimal effects during periods of no rainfall since DIS tidal level governs. Critical sections were also identified that needs flood walls on top of the channel improvement. The flushing technique was shown to be effective in increasing flow velocities for the transport of wastes and sediment matters from upstream to downstream. As a result of this research, it is recommended therefore that regular dredging and flushing of Estero de Paco be done to improve both the hydraulic capacity and water quality condition of the channel. Proper planning and management of the operations will just have to be outlined.